2019
DOI: 10.1021/acs.orglett.9b03850
|View full text |Cite
|
Sign up to set email alerts
|

Redox-Neutral Borylation of Aryl Sulfonium Salts via C–S Activation Enabled by Light

Abstract: Reported here is a novel photoinduced strategy for the borylation of aryl sulfonium salts using bis­(pinacolato)­diboron as the boron source. This method exploits redox-neutral aryl sulfoniums to gain access to aryl radicals via C–S bond activation upon photoexcitation under transition-metal-free conditions. Therefore, it grants access to diverse arylboronate esters with good performance from easily available aryl sulfoniums accompanied by mild conditions, operational simplicity, and easy scalability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 95 publications
(31 reference statements)
1
28
0
2
Order By: Relevance
“…The authors suggested that these products form predominantly via heterolytic cleavage and formation of ionic intermediates, although they also suggested that a pathway involving homolytic cleavage and radical intermediates was possible. As shown here, the direct photolysis of sulfonium salts is generally an inefficient process . Herein, we describe how photocatalysis has enabled the application of sulfonium salts in light‐mediated transformations.…”
Section: Early Reports On the Photochemistry Of Sulfonium Saltsmentioning
confidence: 96%
“…The authors suggested that these products form predominantly via heterolytic cleavage and formation of ionic intermediates, although they also suggested that a pathway involving homolytic cleavage and radical intermediates was possible. As shown here, the direct photolysis of sulfonium salts is generally an inefficient process . Herein, we describe how photocatalysis has enabled the application of sulfonium salts in light‐mediated transformations.…”
Section: Early Reports On the Photochemistry Of Sulfonium Saltsmentioning
confidence: 96%
“…Given that organosulfur compounds are widely present in natural products, drugs and proteins, our protocol was briefly examined as a viable route for the C−S bond borylation of sulfur-containing molecules, which allows modification of their structures. [54][55][56] Indeed, the C-S bond of diphenyl sulfone 1i could be borylated efficiently to give product 2a in excellent yield. When alkyl phenyl sulfones (1j and 1k) and vinyl phenyl sulfone 1l were used, the borylation occurred selectively at the phenyl-SO 2 bonds to give aryl boronic ester product 2a, while the alkyl boronic esters were merely observed in trace amounts.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, enantioselective construction of new C−C bonds through photoinduced C−S bond activation is still very limited and can be reasonably expected in the future. Furthermore, besides C−C bond formation, the construction of other chemical bonds like C−O bond, [60] C−N bond, [46–49,61] C−B bond, [58,62] C‐F [63] bond and C−S bond [64] and so on through light‐mediated C−S bond cleavage are also interesting and promising fields from the viewpoint of organic synthesis. Beyond reactivity and selectivity, the development of safer and more atom‐efficient catalytic platforms is also required in the design of radical precursors, which often generate large amount of side products during their late‐stage functionalization for new chemical bonds formation and organic synthesis.…”
Section: Discussionmentioning
confidence: 99%